IMPLEMENTASI PERATURAN DAERAH KABUPATEN KAMPAR NOMOR 11 TAHUN 2011 TENTANG PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN TAHUN 2016 (STUDI KASUS DESA PANGKALAN SERIK) - Jaya Handayan; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Siak Hulu Subdistrict is the region with the highest target of receiving land and building tax in Kampar Regency in 2016, but in reality the land and building tax receipts in the area are still relatively low. Pangkalan Serik Village is one of the villages in Siak Hulu Subdistrict with the realization of the lowest land and building tax revenue in 2016 so that it can be said that the Kampar Regency Regional Regulation No. 11 of 2011 concerning Rural Land and Building Taxes and Municipalities is not well implemented in the region. The purpose of this study is to describe the implementation of the Kampar District Regulation No. 11 of 2011 concerning Rural and Urban Land and Building Taxes in Pangkalan Serik Village in 2016 and the factors that contribute to the implementation of the Kampar District Regulation Number 11 of 2011 concerning Land and Building Taxes in Rural Areas and Urban in Pangkalan Serik Village in 2016. The method used in this study is a qualitative approach with descriptive analysis method. The results showed that the implementation of the Kampar District Regulation Number 11 of 2011 concerning Land and Building Taxes for Rural and Urban Areas in Pangkalan Serik Village in 2016 had not been effective. Although in terms of communication, resources, the attitude of the implementor, and the organizational structure has supported the policy, the clarity of information for the community has not been achieved. The inhibiting factor in the implementation of this policy is the limited facilities and infrastructure as well as the low public awareness in paying taxes.Keywords: Policy Implementation, Public Policy